Metodología para la implementación de iot aplicado a la agricultura de precisión - Calva Jiménez, Freddy Francisco (Machala: Universidad Tëcnica de Machala, 2022)
The internet of things is the relationship of real-life objects with technological devices that allow them to connect to each other and systems through the internet or other communication networks in order to transmit and receive data, thus allowing an action to be automated. Traditionally, communication and connectivity were given by technological devices through Wi-Fi, while today there are other networks such as 4G or 5G that promise to be communication platforms between a large number of devices, this advance manages to collect a huge amount of information from anywhere with speed, accuracy, availability and integrity. The internet of things, IoT is an emerging topic of social, economic and technological importance. Currently, there is a mix of products, consumer product, industrial products, sensors and real-life objects with internet connectivity and high capacity. analyzes that promise to transform the way we work and live. IoT projections point to the fact that by the year 2025 there will be more than one hundred thousand devices connected to IoT with a great beneficial impact on the global economy. Although the Internet of Things offers us a large number of benefits, it also poses great challenges such as security, performance and sustainability. Internet of things allows the development of applications in different sectors, industry, transport, commerce, homes, cities, agriculture, among others. The modernization of agricultural practices emerges as a new challenge related to the concept of environmental and economic sustainability of the production process. As a result of these modernized agricultural practices, there is innovation based on technology that allows data to be collected, analyzed, interpreted and applied in the preparation of crops, sowing, sowing and cultivation. As well as, in the processing of agricultural products and in the preventive maintenance of any area. Precision agriculture starts as support for agricultural activities, integrates various technologies in order to optimize the productivity of a crop, guarantee sustainability, minimize environmental impact and make agricultural processes more effective. production, increased productivity and profitability of agricultural enterprises. Currently there is no standard methodology to identify needs and propose possible solutions through methods and tools to be implemented in precision agriculture IoT systems. For this reason, the objective of the project is the comparative analysis of IoT methodologies applied to precision agriculture, to then focus on the development of a new hybrid methodology oriented to the safety and quality of the system, in which the design of methodology for the development of IoT systems through the comparative analysis of agile methodologies implemented based on the Internet of Things, good practices of scientific research and the use of the ISO 9001 methodology. This methodology has four phases. Definition and analysis, Design of prototype, Implementation, and, as a last phase, Deployment and quality. This methodology is proposed based on the comparison of the ACOSO_Meth, INTER-METH and MicroIoT Methodology methodologies. The result of the evaluation of the methodology was carried out using qualitative and quantitative research, allowing to obtain a deep knowledge of the implementation of IoT systems oriented to professionals in the computer science area in the province of El Oro. As a result of the application of the survey, obtained an average of 84,86/100 , according to evaluation parameters it is concluded that the AGRO_IOT methodology complies with the parameters established within the quality of ISO 9001, 2015.
El internet de las cosas es la relación de objetos de la vida real con dispositivos tecnológicos que permiten conectarse entre los mismos y sistemas a través del internet u otras redes de comunicación con el fin de transmitir y recibir datos permitiendo así automatizar una acción. Tradicionalmente, la comunicación y conectividad se daba por dispositivos tecnológicos mediante Wi-Fi, mientras que hoy en día existen otras redes como la 4G o 5G que prometen ser plataformas de comunicación entre gran cantidad de dispositivos, este avance logra recopilar enorme cantidad de información desde cualquier lugar con velocidad, veracidad, disponibilidad e integridad. El internet de las cosas, IoT es un tema emergente de importancia social, económica y tecnológica, Actualmente, existe una combinación de productos, producto de consumo, productos industriales, sensores y objetos de la vida real con conectividad a internet y de gran capacidad de análisis que prometen transformar el modo de trabajar y vivir. Las proyecciones del IoT se orientan a que en el año 2025 existan más de cien mil dispositivos conectados a IoT con un gran impacto beneficioso a la economía global. A pesar de que el internet de las cosas nos ofrece un gran número de beneficios, también plantea grandes desafíos como la seguridad, rendimiento y sostenibilidad. Internet de las cosas permite desarrollar aplicaciones en diferentes sectores: la industria, transporte, comercio, hogares, ciudades, en la agricultura, entre otros. La modernización de las prácticas agrícolas surge como un nuevo desafío relacionado al concepto de sostenibilidad ambiental y económica del proceso de producción. Como resultado a estas prácticas agrícolas modernizadas se tiene la innovación en base a tecnología que permite recolectar datos, analizarlos, interpretarlo y aplicarlos en la preparación de cultivos, siembra, siembra y cultivo. Así como también, en el procesamiento de productos agrícolas y en el mantenimiento preventivo de cualquier área. La agricultura de precisión parte como apoyo a las actividades agrícolas, integra diversas tecnologías con el fin de optimizar la productividad de un cultivo, garantizar la sostenibilidad, minimizar el impacto ambiental y efectivizar los procesos agrícolas. producción, aumento de la productividad y rentabilidad de empresas agrícolas. Actualmente no existe una metodología estándar que permita identificar las necesidades y plantear sus posibles soluciones mediante métodos y herramientas para ser implementados en sistemas IoT de la agricultura de precisión. Por ese motivo, el proyecto tiene como objetivo el análisis comparativo de metodologías IoT aplicadas a la agricultura de precisión, para luego enfocarse en el desarrollo de una nueva metodología híbrida orientada a la seguridad y calidad del sistema, en la cual se detalla el diseño de metodología para el desarrollo de sistemas IoT mediante el análisis comparativo de metodologías ágiles implementadas en base al internet de las cosas, buenas prácticas de la investigación científica y el uso de la metodología ISO 9001. Esta metodología posee cuatro fases. Definición y análisis, Diseño de prototipo, Implementación, y, como última fase, Despliegue y calidad. Esta metodología es planteada en base a la comparativa de las metodologías ACOSO_Meth, INTER-METH y MicroIoT Methodology. El resultado de la evaluación de la metodología se realizó haciendo uso de la investigación cualitativa y cuantitativa permitiendo obtener un conocimiento profundo de implementación de sistemas IoT orientado a profesionales del área informática en la provincia de El Oro. Como resultado de la aplicación de la encuesta se obtuvo un promedio de 84,86/100, según parámetros de evaluación se concluye que la metodología AGRO_IOT cumple con los parámetros establecidos dentro de la calidad de la ISO 9001,2015
Keywords: INTERNET DE LAS COSAS; AGRICULTURA DE PRECISION; SOSTENIBILIDAD; RED DE SENSOR